PERBEDAAN ANTARA AQUATIC EXERCISE DENGAN MCKENZIE EXERCISE DALAM MENURUNKAN DISABILITAS PADA PENDERITA DISCOGENIC LOW BACK PAIN - Susanto, Budi; Adiputra, N.; -, Sugijanto (Sport and Fitness Journal, 2015)
Low Back Pain is one of the most musculoskeletal problem. LBP can cause disability, material loss and biopsychosocial problem. The most effective management for LBP is still discussing in the health practitioner and scientist between Aquatic Exercise or McKenzie Exercise. The aim of this study is to prove the different between Aquatic Exercise with McKenzie Exercise to reduce disability in Discogenic Low Back Pain patients. This study was the true experimental control trial research, with randomized pre-test and post-test design. The study was conducted in Physiotherapy Clinic in Borromeus Hospital Bandung and Melinda Surgery Hospital Bandung. The samples were 19 divided into two groups. Group I with Aquatic Exercise was 9 people and Group II with McKenzie Exercise was 10 people. The measuring instrument in this study was Oswestry Disability Index. Results of the hypothesis used paired t-test and independent t-test. The hypothesis test results showed that both of groups can reduce disability significantly with mean in Group I = 25,9248 ± 3,98214, p value = 0.001 (p < 0.05) and Group II = 16,912 ± 4,0873, p value = 0.001. And between 2 groups there were significant difference with mean = 8,57193 ± 3,66789, p value = 0.032 (p < 0.05). The conclusions where both of Aquatic Exercise and McKenzie Exercise could reduced disability significantly and Aquatic Exercise was better than McKenzie Exercise to reduce disability in Discogenic Low Back Pain patients. This study can be suggested that this Aquatic Exercise program to reduce disability in Discogenic Low Back Pain. The multi center study should be held with longer time and much more subjects. Key
Keywords: Discogenic Low Back Pain, Aquatic Exercise, McKenzie, Oswestry